Whole-Genome Metagenomic Analysis of the Gut Microbiome in HIV-1-Infected Individuals on Antiretroviral Therapy - Bai, Xiangning; Narayanan, Aswathy; Nowak, Piotr; Ray, Shilpa; Neogi, Ujjwal; Sönnerborg, Anders (Frontiers in Microbiology, 2021)
Gut microbiome plays a significant role in HIV-1 immunopathogenesis and HIV-1 associated complications. Previous studies have mostly been based on 16S rRNA gene sequencing, which is limited in taxonomic resolution at genus level and inferred functionality. Herein, we performed a deep shotgun metagenomics study with the aim to obtain a more precise landscape of gut microbiome dysbiosis in HIV-1 infection. A reduced tendency of alpha diversity and significantly higher beta diversity were found in HIV-1 individuals on antiretroviral therapy (ART) compared to HIV-1 negative controls. Several species, such as Streptococcus anginosus, Actinomyces odontolyticus, Rothia mucilaginosa, were significantly enriched in the HIV-1-ART group. Correlations were observed between degree of immunodeficiency and gut microbiome in terms of microbiota composition and metabolic pathways. Furthermore, microbial shift in HIV-1 infected individuals was found to be associated with changes in microbial virulome and resistome. From the perspective of methodological evaluations, our study showed that different DNA extraction protocols significantly affect the genomic DNA quantity and quality. Moreover, whole metagenome sequencing depth affects critically the recovery of microbial genes, including virulome and resistome, while less than 5 million reads per sample is sufficient for taxonomy profiling in human fecal metagenomic samples. These findings advance our understanding of human gut microbiome and their potential associations with HIV-1 infection. The methodological assessment assist in future study design to accurately assess human gut microbiome.